Study on Tribological Properities Of Aluminium Hybrid Composities For Automotive Applications. Issue 1 (April 2021) - Kaviyarasan, K; Saaron, A; Rahuram, K M; Ranjithvel, A; Selvakumar, S
Abstract: Aluminium metal matrix hybrid composites are refined through stir casting method. Aluminium A-356 is reinforced with ceramic particles like Zirconium diboride (ZrB2 ) and Tungsten carbide (WC) in varying weight percentages (ie. 2.5% and 5%). (The purpose is to compare the properties like of the different composite specimens). This work aims to develop aluminium metal hybrid composites for automotive applications and studying its wear characteristics. Due to low density, aluminium metal was chosen. Of the several alloys, A356 is chosen as the matrix material since it has good castability and good strength and low cost. Among the reinforcements, WC possess high durability and good wear support. Stir casting technique embraced to fabricate specimens. Then the casted specimens were machined and subjected to wear testing to examine the tribological properties through Pin on disc tribometer apparatus. The pin specimens were tested under different sliding conditions. Then the specimens were investigate under the (SEM) which is Scanning electron microscope to study the wear structure that occurred in sliding condition.